Histoid leprosy in the era of elimination - Sukumar Dandekeri; Hyacinth Peter Pinto; Ramesh M Bhat; M K Srinath (Wolters Kluwer Medknow Publications, 2013)
Histoid leprosy is a variant of Lepromatous leprosy believed to occur due to a mutant strain of leprosy bacillus called as Histoid Bacillus. It was first described by Wade in 1960 in patients from Phillipines. It occurs in patients relapsing after Dapsone monotherapy, in the presence of Dapsone resistance or at times denovo, presenting with lesions mainly over bony prominences. Herein, we present a case of a 37 year old male who presented with skin coloured raised lesions mainly over the trunk, chest, neck and ears in contrast to its usual site of presentation, associated with tingling sensation over the hands and feet. A histopathological examination of the skin lesion was ordered which revealed sheets of histiocytes and lepra bacilli on hematoxylin and eosin and acid fast staining. On correlating the clinical and histopathological findings we came to a diagnosis of Histoid leprosy. The patient was promptly treated with MB-MDT and followed up.